The Hippo Transducer YAP/TAZ as a Biomarker of Therapeutic Response and Prognosis in Trastuzumab-Based Neoadjuvant Therapy Treated HER2-Positive Breast Cancer Patients - Yuan, Jia-qi; Ding, Nian-hua; Xiao, Zhi (Frontiers in Pharmacology, 2020)
Background: We explored the therapeutic and prognostic effect of YAP/TAZ intensityinHER2-positive breast cancer patients. We also investigated the relationship between YAP/TAZ expression and Trastuzumab-resistance. Methods: We collected clinicopathological information from 397 cases. We evaluated therapeutic and prognostic effect of YAP/TAZ and other variables. We also cultivated Trastuzumab-resistance cell lines and explored relationship between YAP/TAZ and Trastuzumab-resistance. Results: Over-expression of YAP/TAZ was remarkable in Trastuzumab-resistant cells, and so did HER3 and HER2/HER3 heterodimer. Inhibition of YAP/TAZ expression reversed Trastuzumab-resistance.YAP/TAZ deficiency contributed to favorable therapeutic response, and so did hormone receptor insufficiency and chemotherapy dosage inferiority. Deficient YAP/TAZ intensity and abundant hormone receptor intensity contributed to better survival. Over-expression of YAP/TAZ was obvious in recurrent cases in comparison with their matching primary lesions. Prognostic superiority of insufficient YAP/TAZ intensity was more outstanding in hormone receptor negative cases. Over-expression of YAP/TAZ and HER3 was generally synchronous. Absence of HER3 expression in residual lesions might correlate with better breast cancer-free survival. Conclusions: Over-expression of YAP/TAZ as well as HER-3 and HER2/HER3 heterodimer was synchronously remarkable in Trastuzumab-resistant cell lines. Inhibition of YAP/TAZ expression reversed Trastuzumab resistance. Deficient YAP/TAZ intensity as well as insufficient hormone receptor intensity and high chemotherapy dosage contributed to favorable therapeutic response. Deficient YAP/TAZ intensity and abundant hormone receptor intensity contributed to better survival, and so did absence of HER3expression in residual lesions. Prognostic superiority of YAP/TAZ expression depended on hormone receptor status. Cases with synchronous over-expression of YAP/TAZ and HER3 suffered poor survival, which revealed the potential effect of YAP/TAZ-HER2/HER3 crosstalk in prognosis of HER2-positive patients.